Reproductive Isolation in Fragmented Wild Populations of Opuntia streptacantha - MUÑOZ-URIAS, Alejandro; PALOMINO-HASBACH, Guadalupe; HUERTA-MARTÍNEZ, Francisco Martín; PIMIENTA-BARRIOS, Eulogio; RAMÍREZ-HERNANDEZ, Blanca C. (Journal of the Professional Association for Cactus Development, 2006)
During pre-Hispanic times, there were extensive Opuntia forests in the semiarid regions of central Mexico. In the colonial period the migration of the Spanish to these regions promoted land clearing for agricultural activities, a tendency that continues in modern times, ultimately leading to deforestation and fragmentation of wild Opuntia populations. The main objective of this work is to evaluate the effects of fragmentation of Opuntia streptacantha populations on the reproductive success. Pollen-grain germination, rates of pollen-tube growth, fruit and seed set were evaluated in cross-pollinations between isolated populations and compared to within-population crosses. The activity of insects was recorded during the blooming period and chromosome number was recorded in the isolated populations under study. Cross-pollinations between populations significantly reduced the number of pollen tubes that reached the base of style and the ovules, affecting the values of fruit and seed set. This seemed to explain the differences obtained between the control (open pollination) and cross-pollination within population. The two populations under study are octaploid. Cross-pollinations between individuals of isolated populations of O. streptacantha showed low performance of out-crossing as indicated by the low number of pollen tubes that reached the base of the style, the ovules, and the low values of fruit set and seed set.